Pediatric Type II Tibial Spine Fractures: Addressing the Treatment Controversy With a Mixed-Effects Model. Issue 8 (27th August 2019) - Adams, Alexander J.; O'Hara, Nathan N.; Abzug, Joshua M.; Aoyama, Julien T.; ,; Ganley, Theodore J.; Carey, James L.; Cruz, Aristides I.; Ellis, Henry B.; Fabricant, Peter D.; Green, Daniel W.; Heyworth, Benton E.; et al.
Background: Tibial spine fractures, although relatively rare, account for a substantial proportion of pediatric knee injuries with effusions and can have significant complications. Meyers and McKeever type II fractures are displaced anteriorly with an intact posterior hinge. Whether this subtype of pediatric tibial spine fracture should be treated operatively or nonoperatively remains controversial. Surgical delay is associated with an increased risk of arthrofibrosis; thus, prompt treatment decision making is imperative. Purpose: To assess for variability among pediatric orthopaedic surgeons when treating pediatric type II tibial spine fractures. Study Design: Cross-sectional study. Methods: A discrete choice experiment was conducted to determine the patient and injury attributes that influence the management choice. A convenience sample of 20 pediatric orthopaedic surgeons reviewed 40 case vignettes, including physis-blinded radiographs displaying displaced fractures and a description of the patient's sex, age, mechanism of injury, and predominant sport. Surgeons were asked whether they would treat the fracture operatively or nonoperatively. A mixed-effects model was then used to determine the patient attributes most likely to influence the surgeon's decision, as well as surgeon training background, years in practice, and risk-taking behavior. Results: The majority of respondents selected operative treatment for 85% of the presented cases. The degree of fracture displacement was the only attribute significantly associated with treatment choice ( P < .001). Surgeons were 28% more likely to treat the fracture operatively with each additional millimeter of displacement of fracture fragment. Over 64% of surgeons chose to treat operatively when the fracture fragment was displaced by ≥3.5 mm. Significant variation in surgeon's propensity for operative treatment of this fracture was observed ( P = .01). Surgeon training, years in practice, and risk-taking scores were not associated with the respondent's preference for surgical treatment. Conclusion: There was substantial variation among pediatric orthopaedic surgeons when treating type II tibial spine fractures. The decision to operate was based on the degree of fracture displacement. Identifying current treatment preferences among surgeons given different patient factors can highlight current variation in practice patterns and direct efforts toward promoting the most optimal treatment strategies for controversial type II tibial spine fractures.